Analysis of Abbreviations Types and Purposes Found in Influencers' Twitter Accounts with Different Gender - S, Desi Budiati.; Rosita, Nur (English Language and Literature, 2024)
Abbreviation consists of five sorts, which are clipping, blends, acronym, initialism, and contraction. Emphasizing the enduring theme of gender differences in language use, the study contributes to the broader discourse on language and gender by examining how men and women employ abbreviations for distinct purposes. Drawing from the theoretical frameworks of Schendl for classifying abbreviation types and Tannen for understanding gender-specific purposes, the investigation centers on Twitter communication. The primary objective is to elucidate the differential use of abbreviations by men and women influencers and how these choices reflect their communicative objectives. The study uncovers significant disparities: women predominantly utilize clipping, initialism, and contractions, aligning with a focus on politeness, hedging, and interpersonal connections. In contrast, men show a preference for blends and acronyms, suggesting a communication style emphasizing efficiency and clarity. This research contributes to the understanding of how linguistic choices, specifically in abbreviations, serve as markers of gender-specific communication styles. The findings underscore the nuanced ways in which men and women employ abbreviations to achieve distinct communicative goals in the context of social media.